A cognitive perspective on quantification - Kraljević, Marija (2007)
A contrastive analysis of quantifiers in English and Croatian might seem simple enough a task because everyone has at least an intuitive knowledge of what quantifiers are and how they are used. But, when we try to go beyond this intuitive knowledge and produce a systematic description of quantifiers, their structure and meaning, we find the problem to be much more challenging than it seems. There are a few problems that make this kind of analysis difficult. Among them are the differences between the two grammatical traditions – English and Croatian. While English grammars usually have elaborate descriptions of syntagmatic relations (the phrasal structure), Croatian grammars omit this level of linguistic analysis or incorporate some of its parts into descriptions of other linguistic phenomena. This has lead to major misconceptions and inadequate descriptions of some linguistic data. My primary interest is in quantifiers as constituents of noun phrases (this is also a questionable notion, as can be seen from different definitions of quantifiers and their relation to the other words in the phrase). Their status within a phrase determines the agreement of the phrase as a whole to other sentence elements. This is not so obvious in English, which does not have overt morphological markers of agreement between subject and verb, but examples from Croatian will help to shed some light onto the internal structure of phrases containing quantifiers. The problem of the status of quantifiers within a certain phrase causes a lot of confusion in Croatian grammars, because the assumption that a noun is the head of any phrase containing a noun and a quantifier is challenged by the way those phrases agree with the verb (the predicate), which is not determined by the morphological features of the noun, but by the morphological features of the quantifier (for example: Došlo je mnogo ljudi. – a plural masculine subject + a singular neuter predicate). I consider cognitive grammar very suitable for dealing with these problems, and I will try to give some insights into the conceputal basis of quantifiers in Croatian and English.
Poster, ne postoji članak.
Projekt MZOS
ENG